Structural insight into the substrate-binding mode and catalytic mechanism for MlrC enzyme of Sphingomonas sp. ACM-3962 in linearized microcystin biodegradation - Guo, Xiaoliang; Li, Zengru; Jiang, Qinqin; Cheng, Cai; Feng, Yu; He, Yanlin; Zuo, Lingzi; Rao, Li; Ding, Wei; Feng, Lingling (Frontiers in Microbiology, 2023)
Removing microcystins (MCs) safely and effectively has become an urgent global problem because of their extremely hazardous to the environment and public health. Microcystinases derived from indigenous microorganisms have received widespread attention due to their specific MC biodegradation function. However, linearized MCs are also very toxic and need to be removed from the water environment. How MlrC binds to linearized MCs and how it catalyzes the degradation process based on the actual three-dimensional structure have not been determined. In this study, the binding mode of MlrC with linearized MCs was explored using a combination of molecular docking and site-directed mutagenesis methods. A series of key substrate binding residues, including E70, W59, F67, F96, S392 and so on, were identified. Sodium dodecane sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) was used to analyze samples of these variants. The activity of MlrC variants were measured using high performance liquid chromatography (HPLC). We used fluorescence spectroscopy experiments to research the relationship between MlrC enzyme (E), zinc ion (M), and substrate (S). The results showed that MlrC enzyme, zinc ion and substrate formed E-M-S intermediates during the catalytic process. The substrate-binding cavity was made up of N and C-terminal domains and the substrate-binding site mainly included N41, E70, D341, S392, Q468, S485, R492, W59, F67, and F96. The E70 residue involved in both substrate catalysis and substrate binding. In conclusion, a possible catalytic mechanism of the MlrC enzyme was further proposed based on the experimental results and a literature survey. These findings provided new insights into the molecular mechanisms of the MlrC enzyme to degrade linearized MCs, and laid a theoretical foundation for further biodegradation studies of MCs.